Avaliação nutricional de pacientes com insuficiência renal crônica submetidos à hemodiálise em uma clínica de nefrologia em João Pessoa-PB. - Clementino, Arabela Vieira. (2015)
It has been observed that changes in nutritional policy in patients with chronic renal failure undergoing hemodialysis should be diagnosed early and corrected, where their presence may worsen the clinical course of the disease. Evaluate and characterize the nutritional profile of these patients is essential for the prevention and treatment of nutritional disorders, which should regularly monitor the nutritional status and purpose of reducing the risk of infections and other complications. In this context the research investigation aims to characterize the nutritional status of patients with chronic renal failure undergoing hemodialysis clinical nephrology in João Pessoa-PB. The sample consisted of 43 patients of both sexes undergoing hemodialysis in a nephrology clinic in John person. For data collection a clinical record with socioeconomic data was used; information about the disease as the etiology and treatment time; anthropometric and biochemical data. For analysis of the results was performed by Chi square test associations using SPSS 21 software. According to the results, 56% of patients were male, and 23% with mean age between 21-40 years. It was identified that 23% of patients had completed primary education, followed by 21% illiteracy, in which 37% had a minimum wage. It was shown that men had longer hemodialysis averaging 88.19 ± 73.52 months. When the etiology of the IRC Hypertensive nephrosclerosis and chronic glomerulonephritis were the most prevalent in both sexes. It was identified that 63% of women and 54% of men had to be eutrophic according to IMC, is also classified as eutrophic according to DCT. Regarding CB, CMB, and AMBc men were classified as malnutrition, revealing a deficit of muscle mass. It was found that 58% of women met with mild malnutrition according to albumin. In relation to other biochemical indicators only urea and calcium showed no acceptable range for both females as for males. Although no statistical significance between the associations made in this study was found, it was noted that monitoring and nutritional routine monitoring in patients with IRC are key to preventing nutritional disorders commonly observed in these patients